Examining the Impact of Transformational Leadership on Knowledge Sharing: The Mediating Effect of Organizational Commitment - Amin, Muhamamd Sirojuddin; Sudarmiatin, Sudarmiatin (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
This study aims to investigate the relationship pattern between transformational leadership and knowledge-sharing behavior, focusing on the role of organizational commitment as a mediating variable. This study was conducted on 269 Micro, Small, and Medium Enterprises (MSMEs) employees in Sukun District, Malang City. The path analysis method was used to test the proposed hypothesis. The analysis results showed that organizational commitment has a significant positive impact on knowledge-sharing behavior among employees. This finding suggests that when employees feel emotionally and rationally attached to the organization, they are more likely to share knowledge. On the other hand, although transformational leadership does not directly affect knowledge-sharing behavior, its influence becomes more pronounced through organizational commitment, which acts as a mediator in the relationship. The results of this study provide valuable insights for MSME actors about the importance of building organizational commitment to encourage a culture of knowledge sharing, as well as the pressure of the need for leaders who can inspire and motivate employees.